2014
DOI: 10.1111/jgs.13022
|View full text |Cite
|
Sign up to set email alerts
|

Do Gerontology Nurse Specialists Make a Difference in Hospitalization of Long‐Term Care Residents? Results of a Randomized Comparison Trial

Abstract: Residents of long-term care facilities have highly complex care needs and quality of care is of international concern. Maintaining resident wellness through proactive assessment and early intervention is key to decreasing the need for acute hospitalization. The Residential Aged Care Integration Program (RACIP) is a quality improvement intervention to support residential aged care staff and includes on-site support, education, clinical coaching, and care coordination provided by gerontology nurse specialists (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 25 publications
1
47
0
2
Order By: Relevance
“…Development of safe intervention protocols to treat common acute conditions affecting the NH resident population can aim resources at programs to be piloted, measured, and funded if they demonstrate a significant effect on ED transfers. Some early interventions include point-of-care testing and building partnerships with community diagnostic organizations to expedite treatment, access to clinical nurse specialists, 36 NPs, 37 communication protocols for handover of information, 38 telemedicine, 39 and symptom alert systems for front-line NH care aide staff. 40 As more than 50% of NH-ED transfers lead to hospital admissions, interventions to reduce ED admissions are highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Development of safe intervention protocols to treat common acute conditions affecting the NH resident population can aim resources at programs to be piloted, measured, and funded if they demonstrate a significant effect on ED transfers. Some early interventions include point-of-care testing and building partnerships with community diagnostic organizations to expedite treatment, access to clinical nurse specialists, 36 NPs, 37 communication protocols for handover of information, 38 telemedicine, 39 and symptom alert systems for front-line NH care aide staff. 40 As more than 50% of NH-ED transfers lead to hospital admissions, interventions to reduce ED admissions are highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on models such as the Gold Standards Framework in Care Homes (GFSCH)36 in the UK, and the residential aged care integration programme (RACIP)37 study (involving gerontology ARC outreach) in New Zealand, as well as results from the present study, the new model includes clinical coaching, and role modelling of both elements are shown to be successful in sustaining knowledge transfer 38. Staff in the current study indicated difficulty identifying when a palliative approach should be initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Given this context and future expectations of an increasingly older U.S. demographic, it is critical that geriatric models of care consider care and cost‐effectiveness outcomes equally as we address “doing more with less.” Contributing to our knowledge at this critical junction are the results presented by Boyd and colleagues in this month's Journal of the American Geriatrics Society . This group specifically examined whether the use of advanced practice nurses (APNs) influenced rates of hospitalization in 29 New Zealand residential aged care (RAC) facilities.…”
mentioning
confidence: 88%
“…This editorial describes the environment in which we are implementing geriatrics models of care. We will provide some reflections on the article by Boyd and colleagues in this month's Journal of the American Geriatrics Society , and we will note how this study compares with prior descriptions of the use of advanced practice nurses in long‐term care settings. We will conclude with some ideas about strategies to do more with less.…”
mentioning
confidence: 99%